Identifikasi Penyebab Terjadinya Kecacatan pada Produk Induktor Toroidal dengan Menggunakan Metode Fault Tree Analysis (FTA) di CV. Cipta Karya Mandiri - Siti Rohmah Fauziah; Puti Renosori; Selamat (UNISBA Press, 2022)
Abstract. CV. Cipta Karya Mandiri is a company engaged in the manufacture of electronic device spare parts in the form of toroidal inductors. Based on the results of the study, in 2020 the company experienced a significant increase in demand compared to 2019. However, it turns out that there is a problem at the company, namely an increase in the percentage of toroidal inductor defects. This shows that the company's efforts to reduce product defects are still not optimal. So that the company needs to know the cause of disability as effort to reduce and eliminate defects that occur. The purpose of this study is to identify the causes of defective toroidal inductor products. The method used to reduce or even eliminate toroidal inductor product defects is by using the Fault Tree Analysis (FTA) method. The process of identifying the causes of failure is carried out on five types of defects which are included in 80% of the cumulative defects on the Pareto diagram. As for what is included in the 80% cumulative Pareto diagram defects consist of loose winding defects, bad windings, bonding overs, red pins, and wound wires. The results of the identification of the causes of defects from the five types of defects using fault tree analysis (FTA), namely the factors that cause defects to consist of human or worker factors, machine factors, and tools used during the production process. Abstrak.CV. Cipta Karya Mandiri is a company engaged in the manufacture of electronic device spare parts in the form of toroidal inductors. Based on the results of the study, in 2020 the company experienced a significant increase in demand compared to 2019. However, it turns out that there is a problem at the company, namely an increase in the percentage of toroidal inductor defects. This shows that the company's efforts to reduce product defects are still not optimal. So that the company needs to know the cause of disability as effort to reduce and eliminate defects that occur. The purpose of this study is to identify the causes of defective toroidal inductor products. The method used to reduce or even eliminate toroidal inductor product defects is by using the Fault Tree Analysis (FTA) method. The process of identifying the causes of failure is carried out on five types of defects which are included in 80% of the cumulative defects on the Pareto diagram. As for what is included in the 80% cumulative Pareto diagram defects consist of loose winding defects, bad windings, bonding overs, red pins, and wound wires. The results of the identification of the causes of defects from the five types of defects using fault tree analysis (FTA), namely the factors that cause defects to consist of human or worker factors, machine factors, and tools used during the production process.